2017
DOI: 10.15294/jpii.v6i1.9599
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Training Needs’ Questionnaire in order to Arrange Science Teacher Training Program

Abstract: An ideal teacher training program is by participant's need. The major aim of this study is getting information about science teacher's perception and needs in their professional's life as a science teacher in Junior High School. The main idea of teacher training is to strengthen the integrated science of Natural Science concepts and problembased learning. Data is gathered by spreading training needs questionnaire to 20 science teachers under an education foundation in Bandung. The questionnaire consists of six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The prior information of teachers' perception has an important role in designing the training program. In line with Tapilouw et al (2017) who stated that the training program of science teachers need to be designed according to teachers' need and prior knowledge. The teacher's understanding of both concepts is shown in Table 2.…”
Section: Resultsmentioning
confidence: 94%
“…The prior information of teachers' perception has an important role in designing the training program. In line with Tapilouw et al (2017) who stated that the training program of science teachers need to be designed according to teachers' need and prior knowledge. The teacher's understanding of both concepts is shown in Table 2.…”
Section: Resultsmentioning
confidence: 94%
“…When all the results obtained after examining the findings are taken into consideration, it can be asserted that pre-service teacher candidates' understanding of PBL approach through experience is effective for them in reaching a level where they can use this approach in their professional lives. This idea is supported by the view that it is important to develop teaching materials appropriate to the problem-based learning approach in teacher education, as mentioned by most of the teachers who have participated in Tapilouw, Firman, Redjeki and Chandra (2017)'s studies.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…This confusion may have arisen because PBL is a constructivist approach to learning, as the literature explored in this systematic review shows; educators promoting constructivist learning in their classrooms may simply present it as a PBL process without due attention to the problem design and implementation processes of PBL, which can be complex and timeconsuming. Tapilouw et al [32] concluded in their study that preservice science teachers have difficulties in implementing problem-based learning and suggested that problembased learning materials should be incorporated into the science-teacher-training program to reduce the obstacle. This aligns with the views of DeSimone [14], who suggests that teachers must engage in effective self-regulatory thinking and actions to address problems by selecting and evaluating critical and relevant resources to meet the needs of students as well as working collaboratively with other teachers in a PBL environment.…”
Section: The Challenges Of Implementing Pbl In the Classroommentioning
confidence: 99%